SISTEM PENGELOLAAN USAHA KOPERASI SIMPAN PINJAM KOPPONTREN AL-MASHDUQIAH PATOKAN KRAKSAAN PROBOLINGGO - Himami Firdausi; Yeni Fatur Rohmah; Raudhatul Jannah; Devi Amaliya Putri; Sonia Puspita Dewi (IZZI: Jurnal Ekonomi Islam, 2024)
Based on the Decree of the Minister of State for Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No.96/KKEP/M.KUKM/IX/2004 article (1) savings and loan cooperatives are cooperatives whose activities include savings and loan businesses carried out to collect funds and channel them through cooperative activities savings and Loan. The benchmark area, Kraksaan sub-district, Probolinggo district has a cooperative unit that operates in savings and loan programs. There are several types of things that the Kopontren al-Mashduqiah savings and loan cooperative unit can do, in the benchmark area, Kraksaan sub-district, Probolinggo district. These are SIJARI savings and loans () which are savings that can be withdrawn every day, TAJIROH (hajj and umrah savings) special savings for Hajj and Umrah and SAFITRI () savings that can only be withdrawn during Eid al-Fitr. Vehicle BPKB register in collaboration with Sikopdit Malang banking management. To apply for a loan, customers apply for a loan, then complete the requirements, then the cooperative department will survey the field, find out the person's character, look for information about the person, then the customer's ability to pay, and find out whether the business the customer is running can cover the loan. will be submitted, then the customer provides collateral, if in ACC, then the loan can be processed. However, this is different from businesses where the process is quite long, such as agriculture where the harvest period takes approximately 4-6 months, so the service is taken at the beginning because it is feared that the customer will forget to pay for the service. . This research aims to determine the development of the Al-Mashduqiah Kopontren savings and loan business in the last three years. This service method is field service.